2021
DOI: 10.15403/jgld-3622
|View full text |Cite
|
Sign up to set email alerts
|

Liver-related Mortality is Increased in Lean Subjects with Non- alcoholic Fatty Liver Disease Compared to Overweight and Obese Subjects

Abstract: Background and Aims: Although non-alcoholic fatty liver disease (NAFLD) is linked to obesity, a proportion of lean subjects also have NAFLD with potentially distinct clinical features. We studied the outcome of lean NAFLD subjects. Methods: 299 consecutive patients (215 male, 84 female, 49.5 ± 13.5years) with biopsy-proven NAFLD and a follow-up of 8.4 years (±4.1; range: 0.9-18.0) were stratified by body mass index (BMI) at the time of liver biopsy: lean (BMI ≤25.0 kg/m, n=38), overweight (BMI 25.0-29.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
1
16
1
Order By: Relevance
“…Compared to the participants with normal BMI and non‐NAFLD, the LN group had a higher risk of death, but the ON and ONN groups (mainly overweight to class I obesity) had a lower risk. The results are consistent with other studies that individuals classified as normal weight or underweight may have higher all‐cause mortality, [ 26 , 27 ] representing a “lean paradox.” [ 8 ] In addition, the LN group in our population increased the all‐cause mortality risk by 52% and liver‐related mortality risk by 177% compared to the ON group, consistent with the results in other cohort studies that reported a positive association between LN and all‐cause mortality [ 14 , 15 , 17 ] and liver‐related mortality [ 28 , 29 ] compared with the ON group. Participants with LN may be individuals who are lean as characterized by a relatively low leg‐fat mass and high subcutaneous abdominal fat mass.…”
Section: Discussionsupporting
confidence: 91%
“…Compared to the participants with normal BMI and non‐NAFLD, the LN group had a higher risk of death, but the ON and ONN groups (mainly overweight to class I obesity) had a lower risk. The results are consistent with other studies that individuals classified as normal weight or underweight may have higher all‐cause mortality, [ 26 , 27 ] representing a “lean paradox.” [ 8 ] In addition, the LN group in our population increased the all‐cause mortality risk by 52% and liver‐related mortality risk by 177% compared to the ON group, consistent with the results in other cohort studies that reported a positive association between LN and all‐cause mortality [ 14 , 15 , 17 ] and liver‐related mortality [ 28 , 29 ] compared with the ON group. Participants with LN may be individuals who are lean as characterized by a relatively low leg‐fat mass and high subcutaneous abdominal fat mass.…”
Section: Discussionsupporting
confidence: 91%
“…6,13 In a small longitudinal study, lean participants with biopsy-confirmed NAFLD followed for a median of 8.4 years had a higher risk of liver-related death compared with overweight or obese participants with NAFLD, although those with lean NAFLD had a higher prevalence of advanced fibrosis at baseline in this study. 18 A larger longitudinal study of more than 1300 subjects with biopsy-confirmed NAFLD from Europe and Australia found that those with lean NAFLD had less severe histologic disease compared with those with nonlean NAFLD. 19 Despite these differences, over about 7.5 years of follow-up, nearly 5% of those with lean NAFLD reported liver-related events, even though the vast majority maintained a lean BMI.…”
mentioning
confidence: 99%
“…First, liver-related disease ranked as the leading or top three causes of death in biopsy-based studies. [12][13][14] This likely represents selection bias, with overrepresentation of patients with more advanced disease. Likewise, some studies included patients with cryptogenic cirrhosis and other chronic liver diseases in the cohort and might have introduced bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence and ranking of liver‐related deaths depended on a number of factors (Table S11). First, liver‐related disease ranked as the leading or top three causes of death in biopsy‐based studies 12–14. This likely represents selection bias, with overrepresentation of patients with more advanced disease.…”
Section: Discussionmentioning
confidence: 99%